Innovative Pedagogies in Indonesian Islamic Schools: Shaping Future Leaders for a Democratic and Just Masyarakat Madani - Susanti, Sinta Ari; Murfi, Ali; Hakim, Ade Anggian; Pranata, Mohamad Waskita Adi (Global Educational Research Review, 2024)
Purpose – This study explores the pedagogical approaches and curricula adopted by Islamic schools in Indonesia to prepare students as future leaders of a civil society, known as "Masyarakat Madani." Given the critical role of education in shaping future leaders, the study investigates how these schools integrate democratic values, social justice, and active citizenship into their educational practices. Methods/Design/Approach – Employing an exploratory case study design, this research examines selected Islamic schools renowned for fostering leadership qualities and civic engagement among students. Data were collected through semi-structured interviews, classroom observations, and document analysis. Participants included teachers, school principals, and alumni from five Islamic schools. Findings – The study identifies innovative pedagogical strategies that Islamic schools use to embed Masyarakat Madani principles in their curricula. These include integrating religious teachings with secular subjects and emphasizing collaborative learning and interactive discussions. Extracurricular activities such as debates, scouting, and student organizations play a significant role in developing leadership skills and active citizenship. However, challenges such as limited resources and insufficient government support were also noted. Originality/Value – This research contributes to the literature on Islamic education by highlighting the potential of Islamic schools in Indonesia to produce leaders who are oriented towards civil society. The study offers practical insights into how these schools can overcome existing challenges and enhance their role in fostering inclusive and sustainable education. Practical Implications – The findings suggest that Islamic schools could serve as models for integrating civic values into education. To optimize outcomes, increased financial support, teacher training, and community involvement are recommended. Effective use of technology in teaching could further strengthen the application of Masyarakat Madani values in daily life. Keywords Islamic education, Masyarakat Madani, leadership development, civic education, Indonesia Paper type Research paper